The Effect Of Islamic Education Learning On Students’ Naturalistic Intelligence: An Ecotheological Perspective - Ferry Aldiansyah; Bahar Agus Setiawan; Hairul Huda (AFKARINA: Jurnal Pendidikan Agama Islam, 2026)
Islamic Education learning has a strategic role in shaping student's characteristic, including developing Naturalistic Intelligence as part of the 21st century holistic education. Naturalistic Intelligence is important to instil so that students have concern, responsibility, and awareness of the environment as part of the values of Unity of God. However, in practicing, Islamic Education learning still tends to be oriented towards the cognitive aspect and still has not been fully integrated to the strengthening of Naturalistic Intelligence. Based on this, the research question of this research is there a significant effect between Islamic Education learning and Student's Naturalistic Intelligence. This research is used quantitative research with associative research. This research was conducted at SMP DARUT TAUHID. This research instrument was a questionnaire that arranged according to the learning variable indicators of Islamic Education and Naturalistic Intelligence. The research population was all students of SMP DARUT TAUHID with a sampling technique used total sampling. The data analysis was conducted through prerequisite test (validity, normality, and linearity) and the simple linear regression analysis. The result of the research indicate that all variables are fulfil the validity, normality, and linearity tests. The regression analysis showed a positive and significant effect of Islamic Education learning on student’s Naturalistic Intelligence with a coefficient of 0.789 or 78.9%. The conclusion of this research is Islamic Education learning has a strong effect on the development on student’s Naturalistic Intelligence, so the integration of Islamic values and environment awareness needs to be strengthened in the learning process.